2015
DOI: 10.1042/cs20140428
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps muscle weakness and atrophy are associated with a differential epigenetic profile in advanced COPD

Abstract: Epigenetic mechanisms regulate muscle mass and function in models of muscle dysfunction and atrophy. We assessed whether quadriceps muscle weakness and atrophy are associated with a differential expression profile of epigenetic events in patients with advanced COPD (chronic obstructive pulmonary disease). In vastus lateralis (VL) of sedentary severe COPD patients (n=41), who were further subdivided into those with (n=25) and without (n=16) muscle weakness and healthy controls (n=19), expression of muscle-enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 70 publications
(133 citation statements)
references
References 53 publications
10
118
3
2
Order By: Relevance
“…1B). Finalmente, también se ha demostrado que mecanismos como la proteólisis, la apoptosis, la autofagia y la epigenética están involucrados en la fisiopatología de la disfunción muscular periférica de dichos enfermos 9,[15][16][17][18][19] .…”
Section: Disfunción Muscular Periférica (Cuádriceps)unclassified
See 1 more Smart Citation
“…1B). Finalmente, también se ha demostrado que mecanismos como la proteólisis, la apoptosis, la autofagia y la epigenética están involucrados en la fisiopatología de la disfunción muscular periférica de dichos enfermos 9,[15][16][17][18][19] .…”
Section: Disfunción Muscular Periférica (Cuádriceps)unclassified
“…2B). Sin embargo, en la EPOC avanzada, idénti-cos mecanismos biológicos 8,9,[15][16][17][18][19]26 a los descritos en la disfunción muscular periférica afectarían al diafragma predominando sobre los mecanismos adaptativos ( fig. 2B).…”
Section: Disfunción Muscular Respiratoriaunclassified
“…A cross-sectional study has shown that global DNA hypermethylation is associated with inflammation and increased mortality in CKD [24]. Recent evidence has shown that mi-RNAs may not only play an important role in the epigenetic regulation of vascular abnormalities in chronic organ disease [25], but also in the pathogenesis of muscle wasting [26]. A downregulation of miR-1 was associated with an increase in histone deacetylase 4 in the vastus lateralis muscle of COPD patients.…”
Section: Epigenetic Alterationsmentioning
confidence: 97%
“…A fibre-type switch towards a less fatigue-resistant phenotype (from slow-twitch to fast-twitch fibres) is a major feature in the vastus lateralis of patients with advanced COPD [33][34][35][36] . Furthermore, fast-twitch fibres are also of smaller size in patients with advanced COPD and poor muscle mass [33][34][35] , thus contributing to muscle weakness. Additionally, factors such as aging 37 , malnutrition 38 , and systemic corticosteroid treatment 39 may worsen the fasttwitch fibre atrophy observed in COPD.…”
Section: Quadriceps Muscle Dysfunctionmentioning
confidence: 99%
“…1). Other relevant molecular and cellular events that have been shown to mediate muscle mass loss and dysfunction in COPD from different aetiological factors are increased proteolysis 33,35 , apoptosis 62 , epigenetic mechanisms 34,[65][66][67][68] , and increased autophagy 35 ( Fig. 3).…”
Section: Biological Eventsmentioning
confidence: 99%